Media communication as a factor of diaspora self-organization - T. N. Kameneva; K. D. Kunilova; A. V. Tseluiko (Цифровая социология)
Intensively developing information and information and communication technologies contribute to the transformation of the modern international students’ migration process. There is a need to redefine and rethink many concepts, including the concept of diaspora, as well as rethinking the role of Internet technologies in diaspora communication processes, which are formed at several levels: migrant – country of origin and migrant – recipient country. The nature of interactions of a foreign citizen is changing not only with his historical homeland, but also with the state in which he finds himself. It becomes obvious that Internet technologies and Internet communications can influence the process of adaptation of foreign students, as well as the nature of their interactions with compatriots and representatives of other socio-cultural environment. Media communication, which is formed in the Internet, has an impact on the organization of the diaspora, on its self-organization, which requires studying this area, as well as possible aspects of self-organization in new media conditions. In this article, the authors attempt to analyze how modern Internet technologies help a foreign student at various stages of his adaptation to new socio-cultural conditions, also assess the role of Internet technologies in the preparatory stage, when a foreign student is just planning his move and actively searching for reliable information about possible obstacles, problems and opportunities of his stay in a new territory. An important section of the article is the analysis of Internet technologies as a mechanism of diaspora communication, as well as a mechanism for implementing the communicative capital of the diaspora in the process of adaptation of a foreign student and his integration into new socio–cultural conditions and the educational environment of the university.